2017
DOI: 10.1016/j.cpc.2017.02.011
|View full text |Cite
|
Sign up to set email alerts
|

monteswitch : A package for evaluating solid–solid free energy differences via lattice-switch Monte Carlo

Abstract: Lattice-switch Monte Carlo (LSMC) is a method for evaluating the free energy between two given solid phases. LSMC is a general method, being applicable to a wide range of problems and interatomic potentials. Furthermore it is extremely efficient, ostensibly more efficient than other existing general methods. Here we introduce a package, monteswitch, which can be used to perform LSMC simulations. The package can be used to evaluate the free energy differences between pairs of solid phases, including multicompon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The nonparabolic corrections will be important when ρ a (Δ E ) and ρ b (Δ E ) have different widths. The difference is not pronounced in this work, but adiabatic LSMC results for the BCC and HCP polymorphs of zirconium provide an example where the nonparabolic corrections would be needed.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…The nonparabolic corrections will be important when ρ a (Δ E ) and ρ b (Δ E ) have different widths. The difference is not pronounced in this work, but adiabatic LSMC results for the BCC and HCP polymorphs of zirconium provide an example where the nonparabolic corrections would be needed.…”
mentioning
confidence: 73%
“…Jackson et al demonstrated that LSMC simulations can be biased along Δ E to generate the “adiabatic” Landau free-energy F L (Δ E ) . Biased LSMC free-energy calculations have been performed for core-softened fluids, Lennard-Jones solids, solid phases of butane, and body-centered cubic (BCC) and hexagonal close-packed (HCP) phases of zirconium …”
mentioning
confidence: 99%
“…The LSMC and diabat methods show significant promise, but nearly all applications have focused on allotropes, i.e., polymorphs of elemental solids. 53,58,59 The one exception is an LSMC calculation for polymorphs of a united-atom butane model by Bridgwater and Quigley. 60,61 They successfully implemented the LSMC approach by mapping centers of mass, orientations, and internal coordinate displacements from one polymorph to another, but their procedures must be implemented on a case-by-case basis for different molecules.…”
Section: Introductionmentioning
confidence: 99%